IMPROVING STUDENT LEARNING OUTCOMES IN MATHEMATICS WITH THE HELP OF DOMINO MEDIA IN THE MATERIAL OF MULTIPLICATION OF INTEGER NUMBERS IN GRADE VI MI AL KAUTSAR SUKOSARI - Ramlan Mahmud (Sains Global Institut, Indonesia, 2026)
This research is a Classroom Action Research (CAR) conducted on sixth-grade students at MI Al Kautsar Sukosari. The Classroom Action Research was conducted because the mathematics learning outcomes of sixth-grade students on integer multiplication were very low. This low learning outcome was due to students finding mathematics difficult and bored, leading to inactivity in the learning process. Given this problem, a Classroom Action Research (CAR) was conducted using learning media. The learning media used were domino cards for integer multiplication. These domino cards were used to address the low learning outcomes of sixth-grade students at MI Al Kautsar Sukosari. The Classroom Action Research was conducted in two cycles. In cycle 1, student learning outcomes improved, with 73% of students achieving a score of 3.70. In cycle 2, student learning outcomes further improved, with 90% of students achieving a score of 3.70. The improved learning outcomes were due to the use of multiplication domino cards as learning media. Keywords: Learning outcomes, mathematics, domino cards.